Histone Ubiquitination by the DNA Damage Response Is Required for Efficient DNA Replication in Unperturbed S Phase - Schmid, Jonas Andreas; Berti, Matteo; Walser, Franziska; Raso, Maria Chiara; Schmid, Fabian; Krietsch, Jana; Stoy, Henriette; Zwicky, Katharina; Ursich, Sebastian; Freire, Raimundo; Lopes, Massimo; Penengo, Lorenza (Molecular cell, 2018)
Chromatin ubiquitination by the ubiquitin ligase RNF168 is critical to regulate the DNA damage response (DDR). DDR deficiencies lead to cancer-prone syndromes, but whether this reflects DNA repair defects is still elusive. We identified key factors of the RNF168 pathway as essential mediators of efficient DNA replication in unperturbed S phase. We found that loss of RNF168 leads to reduced replication fork progression and to reversed fork accumulation, particularly evident at repetitive sequences stalling replication. Slow fork progression depends on MRE11-dependent degradation of reversed forks, implicating RNF168 in reversed fork protection and restart. Consistent with regular nucleosomal organization of reversed forks, the replication function of RNF168 requires H2A ubiquitination. As this novel function is shared with the key DDR players ATM, γH2A.X, RNF8, and 53BP1, we propose that double-stranded ends at reversed forks engage classical DDR factors, suggesting an alternative function of this pathway in preventing genome instability and human disease.